PROPHYLAXIS OF PNEUMOCOCCAL INFECTION IN CHILDREN HAS POSITIVE EFFECT ON ALL POPULATION - M.V. Fedoseenko (Вопросы современной педиатрии, 2008)
Modern data of effectiveness prophylaxis of pneumococcal infection in children younger 1 year old with vaccine is presented in this article. Including of 7 - valency pneumococcal conjugated vaccine (PCV-7) in immunization program of some countries resulted in decrease of morbidity as in vaccinated group, as in all population. It was marked that vaccination with PCV-7 plays important pathogenetic role in termination of hidden forms of disease and prevention of spreading of pneumococcal infection, including the most severe types, hardly treated with antibiotics.Key words: children, pneumococcal infection, vaccination.